LOW DOSE SPINAL ANESTHESIA FOR CESAREAN SECTION IN GRAVIDA WITH RHEUMATIC HEART DISEASE - Senapathi, Tjokorda Gde Agung; Budiarta, I Gede; Astuti, Mira Kusuma (Bali Journal of Anesthesiology, 2018)
Cardiac disease in pregnancy remains an important etiology of maternal and fetal morbidity and mortality.1 Mitral stenosis is the most commonly acquired valve lesion encountered in pregnant women and is almost invariably caused by Rheumatic Heart Disease (RHD).1 Pregnancy and peripartum period represent a physiologic burden that may worsen symptoms in even moderate degrees of cardiac disease.1 Consequently, many women are first diagnosed with cardiac disease during pregnancy.1 In this case report, we describe peripartum management of a 38 years old woman with Congestive Heart Failure functional class II, severe Mitral Stenosis, moderate Mitral Regurgitation, moderate Tricuspid Regurgitation because of Rheumatic Heart Disease. She successfully underwent cesarean section in low dose spinal anesthesia using 7 mg hyperbaric bupivacaine intrathecally. This report highlights that low dose spinal anesthesia remains a good option in anesthesia management for cesarean section in gravida with rheumatic heart disease, especially with severe mitral stenosis.Â